PAKAN DAN PERILAKU MAKAN ANOA (Bubalus sp.) DI TAMAN MARGASATWA RAGUNAN, JAKARTA SELATAN - Abdul Haris Mustari; Aidiliana Ufti Prilianti; Burhanuddin Masyud (Media Konservasi, 2015)
This study aimed to identifying  type of feed, feed management, feed and nutrient content analysis of eating behavior anoa at Ragunan Park. The feed was high palatable is banana. Highest percentage of consumption of feed is anoa 2 with an average consumption of as much as 99,54%. An average consumption of day for totality feed revolved 3,30 – 4,04 (averages 3,58 kg). Keywords: anoa, feeding behaviour, food intake